ระบบพื้นคอนกรีตเสริมเหล็กน้ำหนักเบาราคาประหยัด - ธีรชาติ คงหอม (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
From the study of the typical posttension 8-meter concrete slab, it was found that they are generally thick, causing its dead load to be high when compared to its live load, when built according to the Construction Legislation and The Engineering Institute of Thailand (EIT). This led to excessively thick slab system that affects the following: 1. The load bearing of the slabs that changes structure of the groundwork and the pile. 2. The construction budget and completion time. 3. The energy used in construction and building operation. This study tested a slab with the measurements of 0.05 m thickness, 1.20 m width, and 8 m length. Foam is used to replace the concrete in the bottom of the slab to reduce dead weight by 600 kg/m2, but construction cost is still the same as the posttension floor system of the same length. Integrating these concepts to find a new slab type to solve the mentioned issues, it yielded the following results: 1. Weight - the new and old slab systems weigh the same. 2. Construction time - the new design can be constructed 4 days (or 89 percent) faster than the old, from 9 days to 5 days. 3. Construction budget - the new design costs 5,077 baht(or 28 percent) less than the old design.